Nothing is transmissible but thought / Spanish edition of Le Corbusier’s Mise au point - Sequeira, Marta (Journal of Architecture and Urbanism, 2015)
"Book ‘Nothing is transmissible but thought / Spanish edition of Le Corbusier’s Mise au point’ review." Journal of Architecture and Urbanism, 39(2), p. 161-164